2009
DOI: 10.1186/cc8209
|View full text |Cite
|
Sign up to set email alerts
|

Global end-diastolic volume acquired by transpulmonary thermodilution depends on age and gender in awake and spontaneously breathing patients

Abstract: IntroductionVolumetric parameters acquired by transpulmonary thermodilution had been repeatedly proven superior to filling pressures for estimation of cardiac preload. Up to now, the proposed normal ranges were never studied in detail. We investigated the relationship of the global end-diastolic volume (GEDV) acquired by transpulmonary thermodilution with age and gender in awake and spontaneously breathing patients.MethodsPatients requiring brain tumor surgery were equipped prospectively with a transpulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…In addition to the impact of sex on GEDV, the strong impact of age on GEDV revealed in our study seems to be of high clinical relevance. This is in accordance with previous data suggesting an increase in GEDV with older age [31].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In addition to the impact of sex on GEDV, the strong impact of age on GEDV revealed in our study seems to be of high clinical relevance. This is in accordance with previous data suggesting an increase in GEDV with older age [31].…”
Section: Discussionsupporting
confidence: 95%
“…With regard to a mean GEDV of 1415 mL and a reduction of predicted GEDV by about 150 mL in female patients, appropriate adjustment for sex indexation should correct GEDVI for about 10 %. This is also in accordance with data from a study in elective neurosurgical patients [31] that demonstrated a nearly identical sex -specific difference in GEDVI of 131 mL. In addition to the impact of sex on GEDV, the strong impact of age on GEDV revealed in our study seems to be of high clinical relevance.…”
Section: Discussionsupporting
confidence: 94%
“…The GEDV represents a hypothetical measurement of the cardiac volume that assumes all four cardiac chambers to be in diastole simultaneously. Data on 101 patients has been collected one day after a brain tumor surgery, see Wolf et al (2009) for a detailed description of the data. One of the aims of the study was to characterize the dependence of GEDV on age for the population of patients.…”
mentioning
confidence: 99%
“…29 These data from noncritically ill patients demonstrate surprising heterogeneity of values. Tagami et al recently defined a normal EVLWI of 7.3 ± 3.3 ml/kg in a human autopsy study showing that the proposed normal values of 3---7 ml/kg are possibly not appropriate for most clinical scenarios.…”
Section: Raedvmentioning
confidence: 90%